Fluoride Removal from Drinking Water Using Aluminium Oxide Coated Charcoal – effectiveness of repetitive regenerations (University of Khartoum Engineering Journal, 2022)
There are many techniques to remove fluoride from drinking water. However, adsorption was found to be very effective and easy to apply. Along with this line, many studies were done to find an effective and affordable fluoride adsorbent. Activated Alumina (AA), Aluminum oxide coated sand (AOCS), pumice (AOCP), bauxite (AOCB) and charcoal (AOCC) were recently investigated. Nevertheless, AOCC found to be more promising for two reasons: it is cheap and can be regenerated. This paper aims to further contribute to feasibility of AOCC for fluoride removal in order to reduce the operation cost. Batch and continuous flow filter runs were conducted AOCC regenerated batch-wise, and used for the next filter run. AOCC was consequently regenerated three times. The results showed a considerable increase in AOCC fluoride adsorption capacity after each regeneration cycle. Characterization of virgin charcoal, virgin AOCC and regenerated AOCC after the first, the second and the third regeneration cycle, showed that virgin charcoal has highest specific surface area and micro porosity. For virgin AOCC and regenerated AOCC after the first, the second regeneration cycle a reduction in the specific surface area occurred, coupled with a reduction of micro porosity. AOCC after third regeneration cycle showed an increase in specific surface area likely due to aluminum hydroxide deposits on re-coated AOCC surface. Most of the pores after the third regeneration cycle were found to be meso pores. This means that, specific surface area alone cannot explain the increase in the AOCC adsorption capacity after regeneration. The paper recommends investigating the fluoride removal mechanism onto AOCC in order to produce affordable fluoride removal material from drinking water.